Case report: Birth achieved after effective ovarian stimulation combined with dexamethasone in a patient with resistant ovary syndrome - Huiying Li; Tianli Chang; Hongbei Mu; Wenpei Xiang (BMC, 2022)
Abstract Background Resistant ovary syndrome (ROS) is a rare endocrine disorder and there have been few reports of live births by affected patients. As gonadotropin resistance leads immature oocytes, some researchers reported few live births with in vitro maturation (IVM) of oocytes, but IVM is not always successful in ROS patients. Here, we report an original case of ROS, associated with Ig-FSHR in the serum, who achieved a live birth following ovarian stimulation combined with dexamethasone treatment. Case presentation The 30-year-old woman presented with secondary amenorrhea and infertility. Her serum FSH levels were found to be higher than normal, but in discordance with a normal anti-Müllerian hormone (AMH) level and antral follicle count. Genetic investigation found no mutations potentially affecting FSHR. With reference of previous ROS studies, the patient's serum was analyzed for antibodies directed against FSHR and dot blot analysis showed strong reactivity with FSHR. Then, dexamethasone was proposed to the patient, and she successfully became pregnant, finally delivering a healthy girl by caesarean section. Conclusion To our best knowledge, this is the first report of the successful treatment of ROS using ovarian stimulation combined with dexamethasone. In some cases of ROS, high doses of exogenous gonadotropins in combination with immunosuppressive therapy could be an effective approach.